Family life in England and America, 1690-1820.
1 online resource (422 pages).
Keywords: This four-volume collection of primarily newly transcribed manuscript material brings together sources from both sides of the Atlantic and from a wide variety of regional archives. It is the first collection of its kind, allowing comparisons between the development of the family in England and America during a time of significant change. Volume 3: Managing Families, I The sources included here document the economics of running a household, the experience of being a sibling and information on family inheritance and genealogy. Specifics on home economics include information on food and cooking, washing laundry, insurance inventories and plantation accounts.